Dimensi Sosial Emosional Pada Buku Teks Prigel Basa Jawa Kelas X - Wulandari, Dita; Mujimin, Mujimin (Jayapangus Press, 2025)
Good learning is adapted to the mental age of students. In the Kurikulum Merdeka, mental age is grouped into phases. One of the ways to fulfill teaching materials in each phase is using textbooks. The material presented in textbooks must comply with the principles of material development, namely suitability, consistency and adequacy. This research aims to describe the social emotional dimensions of students in the class X Prigel Basa Jawa textbook published by Erlangga. This research uses a qualitative approach with descriptive methods. The data in this research are in the form of reading texts, material descriptions, and practice questions containing aspects of the social emotional development of SMA/SMK/MA students. The data source in this research is the Prigel Basa Jawa textbook published by Erlangga. The data collection technique uses document review techniques. The research instrument in this study uses data cards as a tool in recording research data. The data found was then analyzed using aspects of social emotional development proposed by Wolfinger. The results of the research show that in the Prigel Basa Jawa textbook there are 130 pieces of data containing the social emotional dimensions of SMA/SMK/MA students. After being distributed into social emotional aspects, the research results showed that there were 19 data showing aspects of empathy, 19 data showing aspects of affiliation, 16 data showing aspects of conflict resolution, and 76 data showing aspects of developing positive habits.